The Pedological Context Modulates the Response of Soil Microbial Communities to Agroecological Management - Degrune, Florine; Boeraeve, Fanny; Dufrêne, Marc; Cornélis, Jean-Thomas; Frey, Beat; Hartmann, Martin (Frontiers in Ecology and Evolution, 2019)
Conservation agriculture is based on harnessing and optimizing natural ecological processes such as those mediated by the soil microbiota and represents a very promising approach to overcome the limitations of current conventional practices. Agronomic conservation strategies such as increasing plant diversity at field scale and minimizing soil disturbances such as tillage aim at fostering the presence of beneficial microbial communities to support intrinsic agroecosystem functions and reduce the reliance on agrochemicals and mechanical soil management. However, it remains poorly understood how these positive contributions are modulated by the pedological context. Moreover, only few studies have assessed the management-dependent responses of microbial communities in real-life farming systems. Here, in close association with the farmers and under realistic field conditions, we explored the response of bacterial and fungal community structure to conventional and conservation (using agroecological principles) management regimes across two pedological sites (loamy sand and sandy loam) in Belgium. Microbial diversity was assessed using a DNA metabarcoding approach of ribosomal markers with the Illumina MiSeq sequencing technology. Our results show that different management approaches select for distinct soil microbial communities and that these management-related effects were modulated by the pedological context. Therefore, designing new agricultural systems to foster the presence of beneficial organisms and reduce the level of pathogenic organisms should account for variability in the underlying pedological context.